Bovine besnoitiosis emerging in Central-Eastern Europe, Hungary - Sándor Hornok; András Fedák; Ferenc Baska; Regina Hofmann-Lehmann; Walter Basso (Parasites & Vectors, 2014)
Abstract Background Besnoitia besnoiti, the cause of bovine besnoitiosis, is a cyst-forming coccidian parasite that has recently been shown to be spreading in several Western and Southern European countries. Findings Clinical cases of bovine besnoitiosis were confirmed for the first time in Hungary, by histological, serological and PCR analyses. Conclusions This is the first report of autochthonous bovine besnoitiosis in Central-Eastern Europe. The emergence of bovine besnoitiosis in this region represents a further example, when human activity (i.e. cattle trading) is the main factor involved in the geographical spread of an infectious disease.